An asymptomatic huge hepatocellular carcinoma with intra-atrial tumor thrombus in a patient with chronic hepatitis B viral infection - Kadir DEMİR; Filiz AKYÜZ; Arzu POYANLI; Atilla ÖKTEN (Turkish Journal of Gastroenterology, 2019)
-